Simulations of fracture tests of uncharged and hydrogen-charged additively manufactured 304 stainless steel specimens using cohesive zone modeling. (15th March 2019) - Sung, Shin-Jang; Pan, Jwo; Korinko, Paul S.; Morgan, Michael; McWillliams, Anthony
Highlights: Present J-R curves for uncharged and hydrogen-charged AM steels built by LENS. Identify cohesive energy by comparing computational results and test data. Model crack growth under fully plastic conditions in SE(B) specimens using CZM. Show different values of cohesive strength and energy for different orientations. Show lower cohesive strength for hydrogen-charged AM steels from simulations. Abstract: Fracture tests of uncharged and hydrogen-charged single edge bend specimens of additively manufactured 304 stainless steels are simulated using the cohesive zone modeling (CZM) approach. Two-dimensional plane strain finite element analyses without cohesive elements are conducted to identify the values of cohesive energy. Similar analyses using CZM with the trapezoidal traction-separation laws are then conducted. The best-fit cohesive parameters show the values of cohesive strength for the uncharged specimens are higher than those for the hydrogen-charged ones whereas the value of cohesive energy for the uncharged specimens can be either slightly lower or higher than that for the hydrogen-charged ones.